Asymmetric flows and drivers of herbaceous plant invasion success among Mediterranean-climate regions. Issue 1 (December 2018) - Casado, Miguel; Martín-Forés, Irene; Castro, Isabel; de Miguel, José; Acosta-Gallo, Belén
Abstract Understanding the mechanisms that support the arrival, establishment and spread of species over an introduced range is crucial in invasion ecology. We analysed the unintentionally introduced herbaceous species that are naturalised in the five Mediterranean-climate regions. There is an asymmetry in the species flows among regions, being the Iberian Peninsula the main donor to the other regions. At interregional scale, the species' capacity to spread among regions is related to the ecological versatility of the species in the donor area (Iberian Peninsula). At intraregional scale, the species' capacity to successfully occupy a complete region first depends on the time elapsed from its introduction and afterwards on the degree of occurrence in the region of origin, which is commonly related to its chance of coming into contact with humans. Information on exotic species in their origin region provides insights into invasion process and decision-making to reduce the risks of future invasions.